A FRAMING ANALYSIS OF INDONESIAN NEWSPAPER ON THE ISSUE OF COMMUNITY-BASED TOURISM IN MAGELANG - Satriya, Candra Yudha; Wahyuni, Hermin Indah; Sulastri, Endang (Universitas Mercu Buana, 2024)
Since its inception in 2009, CBT has been a topic of controversy. However, the different discourses on CBT have led to many debates. Which in turn has led to the destructive impact of exploitation by the community. So it is important to analyze the discrepancy of the discourse. This study uses the frame analysis method to examine and understand how CBT in Magelang district, Indonesia, is conceptualized in media discourse. A total of 75 news articles in online media and 40 articles in print media on CBT in Magelang, published between 2017 and 2022, were selected from 9 online media and 2 print media. 5 issue frames and 4 interest groups were identified to organize the entire public discourse on CBT. Furthermore, a media framing analysis with Entman's theoretical approach was conducted on 35 articles published by Kompas Daily. This was done to understand how the main mass media selected issues, highlighted elements, and provided quality responses about CBT development in Magelang. The results of the analysis show that news related to CBT governance, CBT concept implementation, and tourism infrastructure development received more coverage than other rural tourism issues.